KORELASI ANTARA KETERAMPILAN MEMBACA PEMAHAMAN TEKS LAPORAN HASIL OBSERVASI DAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 1 PADANG - Ellya Ratna, Eria Tiffany B., Emidar, (Universitas Negeri Padang, 2017)
The purpose of this research is (1) to know the level of reading comprehension skills of the text of the observation report of the students of class VIII SMP Negeri 1 Padang. (2) to know the level of skill of writing the text of observation result of student of class VIII SMP Negeri 1 Padang. (3) to know how correlation between reading comprehension skill of observation report and writing skill of report result of observation student of class VIII SMP Negeri 1 padang. This research type is quantitative with correlation method. Based on data analysis, to improve the skill of writing the text of the observation result is required reading comprehension skill of the observation report.Â Kata kunci: korelasi, keterampilan membaca pemahaman teks laporan hasil observasi, dan keterampilan menulis teks laporan hasil observasi